Black-hundreds and old believers: frustrated alliance - Andrey Ivanov (Vestnik Pravoslavnogo Svi͡a︡to-Tikhonovskogo gumanitarnogo universiteta. II, Istorii͡a︡, istorii͡a︡ Russkoĭ pravoslavnoĭ t͡s︡erkvi, 2021)
The article studies the relationship between right-wing monarchist parties and unions of the Russian Empire in the early 20th century (Black Hundreds) and Russian Old Believers. Using materials of right-wing party manifestos and speeches of Black-Hundred leaders, the article demonstrates that by and large they construed Old Believers as a valuable resource for extension of the social base of monarchist movement. In an attempt to bring Old Believers to their side, the right-wingers initially gained some ground but could not achieve the wide-sweeping of Old Ritual followers into the ranks of right-wing parties and unions. Drawing on publications in Old Ritual printed media, it is shown that right-wingers overestimated the conservatism of Russian Old Believers, most of whom did not sympathise with the “Ancient Regime” and hoped for its renovation, preferring opposition political forces to right-wing parties. Protection of the dominant position of the Orthodox Church by right-wingers and disinclination to accept the equal rights of Old Believer spiritual leaders by the Orthodox clergy resulted in a situation when Black-Hundred unions began to be left by some Old Believers who previously supported the right-wing monarchist movement. Activists of the Orthodox clergy who were members of right-wing unions and kept on looking on Old Ritual followers as a fringe group and a politically unreliable element also contributed to the reluctance of Old Believers to join Black Hundreds. It appears that from the sacred for Black Hundreds triad “Orthodoxy, Autocracy, and Nationality”, Old Believers were ready to support only the third item, which was obviously insuffi cient for the emergence of an alliance of right-wingers and Old Believers. As a result, for the majority of politically active Old Believers the promises of the opposition to give equal rights to all religious denominations turned to be more seductive than ideological attitudes of right-wingers.